Iscariot : a graphic novel - Vidaurri, S. M. (Archaia, 2015)
"A dying young girl inherits ancient magical powers. When Iscariot, a rebellious magician in an age-old order, secretly bestows powers upon Carson, a dying young girl, he throws generations of magical tradition into chaos. As Carson struggles with not only her new powers, but with returning to life after years of sickness--schoolmates who don't remember her, a mother who has hidden her spiraling depression--she discovers that Iscariot's intentions might not have been as altruistic as it first appeared. Burdened with magic she doesn't understand and pursued by representatives of the order who seek to rebalance their broken system of power, Carson must find a way to shed the weight of the past and create a future that is hers and hers alone."--provided by publisher.